2023
DOI: 10.1002/ehf2.14508
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex activation therapy in patients with heart failure with reduced ejection fraction: a single‐centre experience

Carola Blanco,
Tomas Madej,
Norman Mangner
et al.

Abstract: AimsHeart failure with reduced ejection fraction (HFrEF) is associated with excessive sympathetic and impaired parasympathetic activity. The Barostim Neo™ device is used for electronical baroreflex activation therapy (BAT) to counteract autonomic nervous system dysbalance. Randomized trials have shown that BAT improves walking distance and reduces N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP) levels at least in patients with only moderate elevation at baseline. Its impact on the risk of heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As a result, blood pressure is lowered, and the overall cardiovascular system experiences a more balanced regulation [86]. The Barostim Neo™ device has shown promising results in safely improving clinical symptoms and NYHA functional class in patients with worsening HF [87]. The BeAT-HF study [88] and the HOPE4HF study [89], for instance, have revealed that BAT therapy significantly improved QoL and exercise capacity, and reduced NT-proBNP levels.…”
Section: When Pharmacological Therapy Is Not Enough: Cardiac Contract...mentioning
confidence: 99%
“…As a result, blood pressure is lowered, and the overall cardiovascular system experiences a more balanced regulation [86]. The Barostim Neo™ device has shown promising results in safely improving clinical symptoms and NYHA functional class in patients with worsening HF [87]. The BeAT-HF study [88] and the HOPE4HF study [89], for instance, have revealed that BAT therapy significantly improved QoL and exercise capacity, and reduced NT-proBNP levels.…”
Section: When Pharmacological Therapy Is Not Enough: Cardiac Contract...mentioning
confidence: 99%